Review on wildlife value orientation for ecotourism resource management - Mariapan, Manohar; Lim, Evelyn Ai Lin; Abdul Gani, Arni; S. J., Badariah; N. I., Fatihah; M. Z., Fauzi; J. J., Libes; S., Noordiana; A., Nursyadiq; R., Munieleswar; Puan, Chong Leong (Forestry Department Peninsular Malaysia, 2012)
Wildlife value orientation (WVO) is important in the management of conflicts in ecotourism, particularly in human and wildlife concerns as human-wildlife conflict reported cases have increased in recent years. Therefore, this article systematically reviews literatures on WVO globally from the context of theoretical approach as well as the effect of modernization on values towards wildlife. The theoretical approach highlights the cognitive hierarchy model and the development of four theories that shapes the cultural thought towards wildlife relevant to ecotourism products. By understanding, through integrated empirical investigation, the values people hold towards wildlife, it enables the development of effective decision makings in handling the conflicts in the realm of ecotourism product or resource management.